Faktor - Faktor Yang Mempengaruhi Kejadian Anemia Pada Ibu Hamil Trimester III di Puskesmas Laubaleng Kabupaten Karo Tahun 2023 - Nuriani Br Tarigan; Basaria Manurung (Antigen : Jurnal Kesehatan Masyarakat dan Ilmu Gizi, 2024)
Anemia is a condition of hemoglobin (Hb) levels in the blood (Hb<11gr/dl) which is caused by a lack of nutrients needed for the formation of Hb. This research aims to determine the factors that influence the incidence of anemia in pregnant women in the third trimester at the Laubaleng Community Health Center, Karo Regency in 2023. This type of research is research using an analytical survey with a cross sectional method approach. The population is all pregnant women in the third trimester of the Laubaleng Community Health Center, Karo Regency, namely 58 people. The number of samples used was 58 people obtained using the total sampling technique. The data analysis technique uses chi square. The results obtained in this study were that from 58 respondents, there was an influence between maternal age and the incidence of anemia in third trimester pregnant women, showing that the p value = 0.001 < 0.05. There is an influence between maternal education and the incidence of anemia in pregnant women in the third trimester, showing that the p value = 0.021 < 0.05. There is an influence between maternal knowledge and the incidence of anemia in pregnant women in the third trimester, showing that the p value = 0.010 < 0.05. There is an influence between maternal parity and the incidence of anemia in third trimester pregnant women, showing that the p value = 0.038 < 0.05. It is recommended for health workers to increase education regarding anemia in pregnant women.